Synthesis and study of block copolymer polyarylates - Storozhuk I. P.; Simachev A. D.; Bulkatov D. P.; Filatova E. V.; Orlov M. A.; Kalinnikov A. N. (E3S Web of Conferences, 2023)
In order to reduce the viscosity of a polyarylate melt based on phenolphthalein and terephthalic acid dichloride with a glass transition temperature of 280°C, polyarylate-polysulfone block copolymers with a glass transition temperature of 240 to 260°C capable of processing through a melt at 340°C were synthesized and studied.